Healing the Wounds: An Examination of Veterans Treatment Courts in the Context of Restorative Justice. (March 2015) - Baldwin, Julie Marie; Rukus, Joseph
Controversy exists regarding whether specialized courts, specifically drug courts, adhere to the restorative justice model. Veterans treatment courts (VTCs) are the newest programmatic innovation in the specialized court arena and have not been widely studied to date. This study utilizes data from the first in-depth case study of a VTC and explores whether it embodies the restorative justice ideal. Using both quantitative and qualitative data, we find that the VTC does not fully embody the restorative justice agenda, but it adheres closer to the ideal than drug courts.